NERACA KARBON PADA SISTEM PERTANIAN BERBASIS PENGGUNAAN ABU SISA DARI BAKARAN DI LAHAN GAMBUT PEDALAMAN (Studi kasus pada Budidaya Tanaman Tomat (Solanum lycopersicum) di Kalampangan) Carbon Balance in Farming Systems Based the Use of Ash of Burnt on Inland Peat (The Case Study on Cultivation of Tomato (Solanum lycopersicum) in Kalampangan) - P, Surawijaya,; Yovita, Yovita (AGRIPEAT, 2016)
ABSTRACTThis study aims to: (1) analyzing the balance of carbon in the combustion materials to produce ashburnt on the cultivation of tomato plants (2) analyze the effect of the ash of burn on the physical andchemical properties of peat ombrogen. The results showed that the net balance obtained from thisstudy is negative, this is because the value of the carbon is lost during an emissions in the combustionprocess wood / roots, weeds urchins and groundcover plants prior to obtaining the ashes of burnt oflitter is 0.581 t of carbon/ha is larger than the value of the carbon that is successfully moored by weedsurchins 0.61 t of carbon/ha and litter previous crop (litter plant sweet corn) is 0.437 t of carbon/ ha,only 65, 34% carbon successfully tethered.Keywords: Balance of carbon, peat ombrogen, ash ameliorant and tomato plants.